2012
DOI: 10.4236/abb.2012.37104
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer: Small molecules targeting apoptosis, a prospective approach to safe scientific success

Abstract: Breast carcinoma represents the second leading cause of cancer death in developed countries amongst women. Current cytotoxic chemotherapy plays an important role in the management of patients with hormone-insensitive or metastatic breast carcinoma, although most of them ultimately develop recurrences. Therefore, there is a need for novel targets and treatment strategies in patients with advanced breast carcinoma that is refractory to conventional chemotherapy. This paper summarizes current knowledge on breast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 62 publications
1
2
0
Order By: Relevance
“…BRCA1 tumor suppressor gene induces apoptosis through both intrinsic and extrinsic pathways. However, BRCA1 acts through both P53-dependent and P53-independent pathways and JNK signaling pathway and GADD45 are involved in P53-independent pathway (Fabbro et al, 2004;Ostrakhovitch and Cherian, 2005;Choene et al, 2012;Kim, 2017). The result of the present study showed that the expression of BRCA1 and GADD45 increased following treatment with myricetin.…”
Section: Discussionsupporting
confidence: 43%
See 1 more Smart Citation
“…BRCA1 tumor suppressor gene induces apoptosis through both intrinsic and extrinsic pathways. However, BRCA1 acts through both P53-dependent and P53-independent pathways and JNK signaling pathway and GADD45 are involved in P53-independent pathway (Fabbro et al, 2004;Ostrakhovitch and Cherian, 2005;Choene et al, 2012;Kim, 2017). The result of the present study showed that the expression of BRCA1 and GADD45 increased following treatment with myricetin.…”
Section: Discussionsupporting
confidence: 43%
“…BRCA1 induces cell apoptosis in both TP53-dependent and TP53-independent pathways. In TP53-independent pathway, c-Jun N-terminal kinase (JNK) signaling pathway and the GADD45 gene are involved (Fabbro et al, 2004;Ostrakhovitch and Cherian, 2005;Choene et al, 2012;Kim, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, deposition of β-catenin transferred from cytoplasm to the nucleus and activated the transcription genes mediated by T-cell factor/lymphoid enhancer factor (TCF/LEF) related to the formation of breast tumor [20,21]. However, as the downstream gene of the Wnt/β-catenin signaling pathway, c-Myc affects the tumor cell cycle by inhibiting growth suppression gene transcription and was significantly increased in Tun + Li group compared with Tun treatment (Figure 3(c)), which could lead to poor survival and continuous growing of MDA-MB-231 cells [22]. Recently, Xu et al also found similar experiment results and investigated the possibility that Schisandrin A could suppress the cell cycle and introduce apoptosis of cells in TNBC though the Wnt/ER stress signaling pathway.…”
Section: Discussionmentioning
confidence: 99%